2014
DOI: 10.2139/ssrn.2423753
|View full text |Cite
|
Sign up to set email alerts
|

Americans, Marketers, and the Internet: 1999-2012

Abstract: This is a collection of the reports on the Annenberg national surveys that explored Americans' knowledge and opinions about the new digital-marketing world that was becoming part of their lives. So far we've released seven reports on the subject, in 1999, 2000, 2003, 2005, 2009, 2010, and 2012. The reports raised or deepened a range of provocative topics that have become part of public, policy, and industry discourse. In addition to these reports, I've included three journal articles -from I/S, New Media & Soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 44 publications
1
15
1
Order By: Relevance
“…This inconsistency is often referred to as the "privacy paradox" (e.g., Kokolakis, 2017, p. 122). Previous scholars have explained this by referring to the idea of a rational cost-benefit analysis (e.g., Draper, 2017;Westin, 2003); people's poor knowledge (Turow et al, 2014; see also above); and notions of a resignation toward privacy (Dencik and Cable, 2017;Draper and Turow, 2019;Hargittai and Marwick, 2016). These findings informed this study's research design and instruments.…”
Section: Critical Big Data Literacymentioning
confidence: 99%
“…This inconsistency is often referred to as the "privacy paradox" (e.g., Kokolakis, 2017, p. 122). Previous scholars have explained this by referring to the idea of a rational cost-benefit analysis (e.g., Draper, 2017;Westin, 2003); people's poor knowledge (Turow et al, 2014; see also above); and notions of a resignation toward privacy (Dencik and Cable, 2017;Draper and Turow, 2019;Hargittai and Marwick, 2016). These findings informed this study's research design and instruments.…”
Section: Critical Big Data Literacymentioning
confidence: 99%
“… 2. In addition to the possibility of targeting registered voters who may not agree with the candidate’s issue position, the use of narrowly targeted messaging can be risky if recipients recognize that the campaign is using tailored messages based on data that it has purchased or otherwise obtained without the recipient’s consent. In a 2012 survey, large majorities reported that they would be less likely to support a candidate using this type of tailored messaging (Turow, Carpini, Draper, & Howard-Williams, 2012). …”
mentioning
confidence: 99%
“…In a risk management culture, consumer complaints are regarded less as an essential expression of the right to control one's personal information, and more as something to be minimized. Criticisms of self-regulation in the United States have been long-standing and persistent (Turow, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%